ISLAM AND STRENGTHENING CIVIL SOCIETY (THE PORTRAIT OF THE EXPERIENCES OF NAHDLATUL ULAMA (NU) AND MUHAMMADIYAH) - Jufri, Andi (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2022)
Socio-religious organizations have an important and specific role in strengthening civil society (Civil Islam) in Indonesia. This article attempts to portray the role of religious organizations, especially NU and Muhammadiyah in strengthening civil society. This research uses a descriptive qualitative method which based on the scholarly literature as books, articles, and documents that are relevant to the research theme. The research data is then reduced, displayed, verified and then concluded. The process of data analysis in this study was carried out according to the stages of research based on discourse analysis techniques, domain analysis, taxonomic analysis, componential analysis and theme analysis. The results of this study indicate that the religious organizations of NU and Muhammadiyah were formed not to pursue pragmatic gains, but are intended as media for educating and empowering the ummah. NU and Muhammadiyah, with their respective character movements, have brilliantly positioned their roles as agents of social change, partners in state dialogue, as well as shields for citizens in dealing with state and market hegemony. In actualizing the intellectual movement and community empowerment, NU and Muhammadiyah have been successful in conditioning the creation of a free public space, a climate of democratic political life, a tolerant social and political life, accepting plurality as a reality and encouraging the strengthening of insights about pluralism and multiculturalism, as well as continuing to fight for social justice. خلاصةتلعب المنظمات الاجتماعية والدينية دورًا مهمًا ومحددًا في تعزيز المجتمع المدني (الإسلام المدني) في إندونيسيا. يحاول هذا المقال تصوير دور المنظمات الدينية ، وخاصة نهضة العلماء والمحمدية في تقوية المجتمع المدني. تستخدم هذه الدراسة طريقة وصفية نوعية تعتمد على مراجعة بيانات المكتبة في شكل كتب ومقالات ووثائق ذات صلة بموضوع البحث. ثم يتم تقليل بيانات البحث وعرضها والتحقق منها ثم الانتهاء منها. تمت عملية تحليل البيانات في هذه الدراسة وفقًا لمراحل البحث بناءً على تقنيات تحليل الخطاب وتحليل المجال والتحليل التصنيفي وتحليل المكونات وتحليل الموضوع. تشير نتائج هذه الدراسة إلى أن مؤسسات نهضة العلماء والمحمدية الدينية قد تم تشكيلها ليس لتحقيق أرباح عملية ، ولكن كان الهدف منها أن تكون وسيلة لتثقيف وتمكين الأمة. لقد حددت NU والمحمدية مع شخصيات حركتيهما ببراعة دورهما كعوامل للتغيير الاجتماعي ، وشركاء في حوار الدولة ، فضلاً عن كونهما دروعًا للمواطنين في التعامل مع هيمنة الدولة والسوق. في تحقيق حركة التمكين الفكري والمجتمعي ، نجحت NU والمحمدية في خلق مساحات عامة حرة ، ومناخ للحياة السياسية الديمقراطية ، وحياة اجتماعية وسياسية متسامحة ، وقبول التعددية كحقيقة وتشجيع تعزيز الرؤى حول التعددية والتعددية الثقافية ، و الاستمرار في النضال من أجل العدالة الاجتماعية.الكلمات المفتاحية: منظمات المجتمع (أورماس) ، جامعة النيل ، المحمدية ، المجتمع المدني ، الإسلام ، إندونيسيا Abstrak Organisasi sosial keagamaan memiliki peran penting dan spesifik dalam penguatan Masyarakat Madani (Civil Islam) di Indonesia. Artikel ini berusaha memotret peran ormas keagamaan khususnya NU dan Muhammadiyah dalam penguatan Masyarakat Madani. Penelitian ini menggunakan metode kualitatif deskriptif yang berbasis pada telaah data kepustakaan berupa buku, artikel, maupun dokumen yang relevan dengan tema penelitian. Data penelitian selanjutnya direduksi, didisplay, diverifikasi dan kemudian disimpulkan. Proses analisis data dalam penelitian ini dilakukan sesuai tahapan penelitian berdasarkan teknik analisis wacana, analisis domain, analisis taksonomi, analisis komponensial dan analisis tema. Hasil penelitian ini menunjukkan bahwa Ormas keagamaan NU dan Muhammadiyah dibentuk bukan untuk mengejar keuntungan yang bersifat pragmatis, tetapi dimaksudkan sebagai media pencerdasan dan pemberdayaan ummat. NU dan Muhammadiyah dengan karakter gerakannya masing-masing telah sangat cemerlang memposisikan perannya sebagai agen perubahan sosial, mitra dialog negara, sekaligus menjadi perisai bagi warga negara dalam berhadapan dengan hegemoni negara dan pasar. Dalam mengaktualisasikan gerakan pencerdasan dan pemberdayaan masyarakat, NU dan Muhammadiyah terbilang sukses mengkondisikan penciptaan ruang publik yang bebas, iklim kehidupan politik yang demokratis, kehidupan sosial politik yang toleran, menerima pluralitas sebagai realitas dan mendorong penguatan wawasan tentang pluralisme dan multikulturalisme, serta terus memperjuangkan keadilan sosial. Kata Kunci: Organisasi masyarakat (Ormas); NU (Nahdlatul Ulama); Muhammadiyah; Masyarakat Madani; Islam; Indonesia